RELIGIOUS ISSUES IN THE 2019 PRESIDENTIAL ELECTION OF INDONESIA - Iswandi Iswandi; Gibran Abdullah (Jurnal Al-Dustur, 2020)
The election of a president and vice president is a fundamental way to fill thevacuum of power. However, in the 2019 presidential election, a striking phenomenon with the involvement of religion in the political contest, so that there are many pros and cons if it does not suitable withthe desire of each religious elite in the 2019 presidential election.The involvement of religion in the presidential election raises questions such as, first, how religion was involved in the presidential election process; Second, how religious discourse takes place in legitimating a particular process in the presidential election; and Third, how does religious involvement in the presidential election bring consequences to the life of society as a whole.The method used in this paper is a qualitative method. The qualitative method is often referred  as the generic qualitative method which is to find out several indications of the 2019 presidential election with the involvement of religion as a marker of identity. While the primary data source obtained from various online media in the form of writing, or in the form of direct coverage, and analysis of the author's using descriptive analysis.During presidential election, the religious elite consider emotional feeling as a priority so that they come out of the core problem. So that religion in the presidential election is only an instrument of political interests and can not be avoided again through movements that ultimately lead to pros and cons among fellow religious elites. Thus the professionalism of religion will be difficult to create because it is caused by religious elites who legitimize religion into the practical politics.